(untitled) (Eurasian Journal of Philology Science and Education, 2024)
The article deals with Russian idea of law in “Crime and Punishment” by Dostoevsky. The synthesis is focused on consideration in religious-utopian context. This approach made to study spiritual, religious nature of crime and punishment as value. Law as category of consciousness draws attention to basis of crime and its connection with “all-humanity”. As the source of crime and possibility of atonement explains philosophy of negation as worldview basis of Raskolnikov’s crime. The connection between sin and freedom explains conflict of values in Raskolnikov’s mind as source of Bonapartism. Dostoevsky’s treatment of individual as bearer of rights characterises writer’s position in relation to Slavophiles, Narodniks and Westerners. The science approach is built on review of works that characterise historical, journalistic context of idea of right. Establishing connection between Russian idea of law and category of all-humanity is basis for concept of “Russian” in Dostoevsky’s work, national identity and construction. The application of methods brings problem into field of philosophy and sociology. It is shown that “all-humanity” implies in Dostoevsky idealised relations between Russians and Europeans, identification of Russian with Jesus. This view is opposed to Solzhenitsyn’s view of Russian-Jewish question. The significance of approach is due to study of Russian philosophy of law. The writer’s development of humanity, connection of Russian idea of law explain essence of axiological interpretation of freedom and sin. The writer shows the idea as “all-human community” through example of Raskolnikov’s spiritual journey to enlightenment of sin. The prospects of topic are connected with process of identity construction, which represents new approach to study of writer’s artistic and journalistic heritage. The obtained results can be used in courses on history of Russian classical novel, special courses on theory of law, philosophical foundations of Russian realism. The practical significance of topic lies in methodology of contextual analysis. Key words: Dostoevsky, values crisis, “all-humanity”, Russian identity.